Socio-scientific Issues in Pre-service Teacher Training - Akalamkam, Kalyani; Sharma, Smriti (THE PRIMARY TEACHER, 2019)
Contemporary educational discourse stresses upon inter-disciplinarity, and incorporation of socio-scientific issues is considered imperative to promote twentyfirst century skills of critical thinking and problem-solving. Research to prepare teachers for incorporating socio-scientific skills in elementary classrooms is still in its nascent stages in the Indian context. This research was undertaken with the aim to capture the processes and pedagogical discourses in the teacher preparation in classroom while building elementary school pre-service teachers’ understanding of socio-scientific issues and to explore the possibilities of incorporating it in primary school classrooms. Qualitative data was gathered from forty three pre-service teachers studying in a four-year undergraduate teacher preparation programme. Through the processes of open coding three themes were identified for analysis: breaking disciplinary boundaries; ‘personalisation’ for meaningful learning; transacting a ‘pedagogy of discomfort’. The paper also discusses the implications for implementing a pedagogy centred around socioscientific issues with primary school children.